THE EFFECT OF IMPLEMENTING PAIKEM USING STUDENT-CENTERED LEARNING, CASE-BASED LEARNING, AND COOPERATIVE LEARNING ON LEARNING EFFICIENCY AND EFFECTIVENESS - I Indrayati (Universitas Brawijaya, 2019)
The learning activities of financial accounting practice in Malang State Polytechnic (also called Polinema) have not been able to generate learning results meeting the real-world needs, in respect of the cognitive, psychomotor and affective aspects. Thereby, the researcher developed a new method in the future learning: PAIKEM (which stands for Pembelajaran Aktif, Inovatif, Kreatif, Efektif dan Menyenangkan - Active, Innovative, Creative, Effective and Fun Learning) using student-centered learning, case-based learning and cooperative learning for efficiency and effectiveness of learning. The purpose of this study is to develop and apply the PAIKEM method with student-centered learning, case-based learning, and cooperative learning to generate high-quality human resources in the accounting department of Polinema for competing in global or international markets. This is explanatory research discussing the effect of teacher-centered learning, student-centered learning, project-based learning, creative learning, effective learning, and fun learning variables on the efficiency and effectiveness of learning. This research employs a population of 400 students and a sample of 180 students taken by purposive sampling with a 5-point Likert scale measurement. The data analysis method utilized multiple linear regressions. The primary data source was collected through documentation from the questionnaire. The results revealed that the project-based learning, cooperative learning, and fun learning variables had a significant effect on efficiency while the teacher-centered learning, student-centered learning, creative learning, and effective learning variables did not significantly affect learning efficiency. Furthermore, student-centered learning, cooperative learning, effective learning, and fun learning variables had a significant effect on learning effectiveness; while the teacher-centered learning, case-based learning, creative learning variables did not.